2021
DOI: 10.3390/nu14010166
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Complications of Type-2 Diabetes

Abstract: The gut microbiota has been linked to the emergence of obesity, metabolic syndrome and the onset of type 2 diabetes through decreased glucose tolerance and insulin resistance. Uncontrolled diabetes can lead to serious health consequences such as impaired kidney function, blindness, stroke, myocardial infarction and lower limb amputation. Despite a variety of treatments currently available, cases of diabetes and resulting complications are on the rise. One promising new approach to diabetes focuses on modulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
176
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(178 citation statements)
references
References 169 publications
(141 reference statements)
1
176
0
1
Order By: Relevance
“…Consistent with our findings, results from animal studies have shown that an increased abundance of R. intestinalis was associated with weight loss and reduced glucose intolerance [ 38 ]. In humans R. intestinalis was shown to be present at lower concentrations in individuals with type 2 diabetes compared to healthy subjects [ 39 , 40 , 41 , 42 ]. Similarly, Bacteroides stercoris (and likely also Bacteroides caccae ) have been identified as butyrate producers [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, results from animal studies have shown that an increased abundance of R. intestinalis was associated with weight loss and reduced glucose intolerance [ 38 ]. In humans R. intestinalis was shown to be present at lower concentrations in individuals with type 2 diabetes compared to healthy subjects [ 39 , 40 , 41 , 42 ]. Similarly, Bacteroides stercoris (and likely also Bacteroides caccae ) have been identified as butyrate producers [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that the development of diabetes is related to changes in the compositional profile of gut microbiota [ 38 ]. Our data indicated that the isolated and purified DPP-IV inhibitory peptides from donkey blood reduced the fasting glucose of type 2 diabetic mice.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, further research is needed to address the effect of the microbiome on additional organs such as the lung, skin, muscles, and kidneys, whose functions could also be influenced by IF diets 190–193 . Moreover, it remains to be determiced what is the role of the IF‐microbiome axis in several T2D‐related complications, such as the susceptibility to fungal infections, 194 diabetic foot ulcers, and diabetic nephropathy, which account for high morbidity and mortality rates in T2D patients 195 . Another question is whether a combination of IF with a defined diet composition or food choice consumed in eating days (eg, the aforementioned 5:2 DASH diet 147 ) can provide targeted benefits for certain CMD‐related conditions.…”
Section: Future Perspectivesmentioning
confidence: 99%
“… 190 , 191 , 192 , 193 Moreover, it remains to be determiced what is the role of the IF‐microbiome axis in several T2D‐related complications, such as the susceptibility to fungal infections, 194 diabetic foot ulcers, and diabetic nephropathy, which account for high morbidity and mortality rates in T2D patients. 195 Another question is whether a combination of IF with a defined diet composition or food choice consumed in eating days (eg, the aforementioned 5:2 DASH diet 147 ) can provide targeted benefits for certain CMD‐related conditions. In this respect, it is worth noting that although the nutrient composition of the diet has a tremendous effect on the gut microbiome, 196 the impact on CMD has not been elucidated.…”
Section: Future Perspectivesmentioning
confidence: 99%